2018
DOI: 10.1002/mds.27298
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative, clinically relevant acoustic measurements of focal embouchure dystonia

Abstract: Acoustic variables distinguish musicians with embouchure dystonia from controls and reflect different types of symptomatic impairments. Our composite acoustic severity score predicts severity of clinical global impression for musicians with different patterns of symptomatic impairment and may provide a foundation for developing a clinical rating scale. © 2018 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
(41 reference statements)
1
6
0
Order By: Relevance
“…We replicated the previous finding that patients with ED exhibited greater variability of F0 signals than HCs during tone production (Lee et al, ; Morris et al, ). Those pioneering studies demonstrated that variability of F0 signals during tone production serves as a hallmark of ED (Lee et al, ; Morris et al, ), supporting the notion that quantification of F0 variability reflects dystonic symptoms of ED.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We replicated the previous finding that patients with ED exhibited greater variability of F0 signals than HCs during tone production (Lee et al, ; Morris et al, ). Those pioneering studies demonstrated that variability of F0 signals during tone production serves as a hallmark of ED (Lee et al, ; Morris et al, ), supporting the notion that quantification of F0 variability reflects dystonic symptoms of ED.…”
Section: Discussionsupporting
confidence: 90%
“…We replicated the previous finding that patients with ED exhibited greater variability of F0 signals than HCs during tone production (Lee et al, ; Morris et al, ). Those pioneering studies demonstrated that variability of F0 signals during tone production serves as a hallmark of ED (Lee et al, ; Morris et al, ), supporting the notion that quantification of F0 variability reflects dystonic symptoms of ED. Although the neural correlates of this symptom had not previously been identified, we found a correlation between F0 variability and brain activity, lending further support to the notion that F0 variability is a reliable behavioral measure for assessing individual differences in ED severity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Palpation of the embouchure is essential to look for tenderness or nodules in order to rule out other causes of embouchure discomfort. 7 Quantification of severity of ED can also be attempted based on acoustic measures 30,31 (Table 1). On studying the acoustic analysis, high registers are most severely affected.…”
Section: Diagnosismentioning
confidence: 99%